Aktifitas Antioksidan Kue Mochi dengan Penambahan Ekstrak Beras Ketan Hitam, Ubi Jalar Ungu dan Buah Bit - Mustofa, Akhmad; Pratiwi, Liana Dewi; Widanti, Yannie Asrie (Universitas Sebelas Maret (UNS), 2023)
Mochi cake is loved by many people because it has a good taste with a soft texture. In general, this cake is made with the main ingredients of glutinous rice, peanuts and cornstarch. Currently, there are many innovations in making mochi cakes with different ingredients. The purpose of this study was to determine the chemical and organoleptic characteristics of mochi cake which has the highest antioxidant activity and is preferred by consumers. The study used a factorial completely randomized design with the first factor being the type of extract (black glutinous rice, purple sweet potato, beetroot) and the second factor being the concentration of the added extract (50%, 70% and 90%). The results showed that the mochi that had the highest antioxidant activity and was favored by consumers was mochi with the addition of purple sweet potato extract with an extract concentration of 70%. The mochi has antioxidant activity characteristics reaching 52.08%; total phenol 276.76 mg GAE/100 g, moisture content 33.17%; 0,23% of ash; 7,04% of protein; 0,13% of fat; total carbohydrates by 59.41%. The organoleptic characteristics of mochi in that treatment were purple color (2,62); quite sticky (3.88); quite chewy (3.37); less off flavor (2.81) and the most preferred overall (3.31). The use of natural pigments that also have antioxidant activity needs to be done to improve the quality of food ingredients.concise and factual abstract is required.